2018
DOI: 10.3390/ijerph15112373
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Caffeine Consumption among Pregnant Women from Southern Poland

Abstract: Caffeine is the most widely consumed stimulant worldwide, including by pregnant women. Products containing caffeine should be limited in accordance with the recommendations for pregnancy. The purpose of this study was to evaluate consumption of caffeinated products and daily caffeine intake from food by pregnant women. The study was conducted on a group of healthy pregnant women: attendees of antenatal classes (n = 70) and patients of an outpatient gynecological clinic (n = 70) from Krakow (Southern Poland). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…To the best of our knowledge, only two studies on caffeine intake during pregnancy have been conducted in Poland so far, and both report optimistic findings. Mean daily caffeine intake was 91 mg/day according to the first study (conducted between 2005–2007) and 50 mg/day according to the second study (conducted between 2014–2015) [28,29]. The current result (68 mg from coffee, tea, and energy drinks) confirmed that consumption of caffeinated products by women in Poland during pregnancy is reasonable and non-excessive.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…To the best of our knowledge, only two studies on caffeine intake during pregnancy have been conducted in Poland so far, and both report optimistic findings. Mean daily caffeine intake was 91 mg/day according to the first study (conducted between 2005–2007) and 50 mg/day according to the second study (conducted between 2014–2015) [28,29]. The current result (68 mg from coffee, tea, and energy drinks) confirmed that consumption of caffeinated products by women in Poland during pregnancy is reasonable and non-excessive.…”
Section: Discussionsupporting
confidence: 57%
“…Tea, whose consumption was declared by 80% of the respondents in this study and 93% in another study, is decidedly more popular and continues to be the main source of caffeine in the diet of pregnant women from Poland [28]. In Poland, black tea is the most popular drink and the main source of daily caffeine intake (44–59% according to the earlier studies [28,29] and 50% according to the current study), and only a small amount is derived from green tea (5–16% according to the earlier studies [28,29] and 13% according to the current study). Tea is also the main source of caffeine in Great Britain [9] and Japan [22], although in Japan, most caffeine in the diet of pregnant women comes from green tea (75%), and only some from black tea (4%).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…When examining whether maternal pre-pregnancy BMI modified the association between caffeine intake and SRS T-scores, we categorized women as obese (BMI: ≥30 kg/m 2 ), overweight (BMI: 25-<30 kg/m 2 ), and normal weight (BMI: 18.5<25 kg/m 2 ) or underweight (BMI: <18.5 kg/m 2 ) [ 67 ]. In HOME, but not EARLI, we observed that pre-pregnancy BMI modified the association between caffeine intake and SRS T-scores (BMI category x caffeine interaction P value = 0.04) (S11 Table in S1 File ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies conducted in New York [25] and United Kingdom [26] also used questionnaires to collect caffeine intake -Food Frequency Questionnaire and CAT Questionnaire. In the assessment of caffeine intake, other authors have considered, as we did, cola products and tea [27] or energy drinks and chocolate [2, 24,28].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%